Investigação de rearranjos cromossômicos no gene BRAF em carcinomas pediátricos da tiroide - Sisdelli, Luiza de Mello Oliveira [UNIFESP] (2017)
The incidence of thyroid carcinoma, mainly of the papillary histological subtype (PTC), has increased in most populations, including pediatric patients. Genetic alterations leading to the MAPK pathway activation are highly prevalent in PTC. It has been demonstrated that BRAF V600E mutation is the most prevalent alteration found in sporadic PTC in adult (~40%). However, this event is rarely identified in pediatric PTC. In contrast, chromosomal rearrangements involving BRAF have been identified, mainly in radiation-exposed pediatric PTC. Our group described, for the first time, the presence of AGK-BRAF fusion in sporadic pediatric PTC. This suggests that it might be an alternative mechanismof aberrant BRAF activation in pediatric cases. Thus, the objective of this work was to investigate rearrangements involving BRAF. In the first part of the study, we performed the investigation on 22 pediatric PTC, by FISH break-apart (FISH BA), 5'RACE and sequencing. By FISH BA, it was revealed four positive cases for the BRAF gene breakage, with 10%, 11%, 17% and 36% of the primary tumor cells carrying the rearrangement. Using 5'RACE and sequencing techniques, it was possible to identify the AGK/BRAF rearrangement in one of them. In the second part of the study, we expanded our analysis to 52 pediatric PTC. AGK/BRAF fusion was investigated by RT-PCR and BRAF V600E mutation by PCR and sequencing methodologies. The AGK/BRAF fusion was identified in 27% of the cases and associated with younger ages while BRAF V600E mutation was found in 8% and associated with older ages. PTC with BRAF alterations tends to have a more aggressive biological behavior.